A novel sulfur-driven autotrophic denitrification coupled with bio-cathode system for bioelectricity generation and groundwater remediation. (15th July 2022) - Cheng, Jianping; Tang, Dai; Tang, Zhiguo; Guo, Jin
Abstract: This study explored the feasibility of treating wastewater using sulfur-driven autotrophic denitrification (SAD) coupled with the bio-cathode of microbial fuel cell (MFC), focusing on simultaneous bioelectricity generation, denitrification, and desulphurization. A maximum output voltage of 360 mV was obtained with a power generation cycle of 25 h when simulated wastewater with 100.0 mg/L of each -N and S 2− -S was employed as the influent in the SAD-BMFC. Compared with solo SAD or MFC, SAD-BMFC obtained a higher -N removal rate (E12 h = 87.7%, E24 h = 100%), and less -N accumulation. S 2− -S of the influent was almost completely removed, oxidized to S 0 -S (88.6–90.2 mg/L) and -S (9.8–11.4 mg/L). The reaction system achieved self-balance of acidity-alkalinity (pH 7.05–7.35). The SAD process was the main pathway for -N removal (80.2%) and a smaller proportion of electrons came from the bio-cathode. This study effectively combined SAD with a bio-cathode system for simultaneous energy harvest and bio-enhanced remediation of groundwater contaminated by both -N and S 2− -S. HIGHLIGHTS: The triple performance of bioelectricity generation, denitrification and desulfurization was realized in the SAD-BMFC. The denitrification efficiency was improved and the power generation performance was weakened due to the addition of S 2− -S. S 2− -S was oxidized to S 0 -S, even -S. The self-balance of acidity-alkalinity (pH = 7.05–7.29) was achieved. Graphical Abstract